Lessons and lessons from the mention of the earthly paradise in the Holy Quran - an objective study - - Kambue, Fadil (Islamic Sciences Journal, 2023)
The research deals with lessons and lessons from the mention of the earthly paradise in the Holy Qur’an. It deals with the verses that have a lesson for those who consider it. The truth, Glory be to Him, mentioned the Qur’anic stories for the lesson and the sermon. The research dealt with God’s honoring of the son of Adam by harnessing the gardens of the earth for his living. It also dealt with the representation of spending in the way of God in a prosperous paradise, as well as dealing with the representation of the expense of hypocrisy in the burning paradise. Denying the right of the poor to Paradise was a cause of its destruction, and the conclusions and recommendations that have been reached are a summary of the research.